IN HOSPITAL OUTCOMES OF PATIENTS WITH ACUTE ST ELEVATION MYOCARDIAL INFARCTION NEEDED TEMPORARY PACEMAKER - YOUSAF, W; ASIF, S; MALIK, SA; KHARL, RAK; KHURSHID, A; ASHRAF, J (Biological and Clinical Sciences Research Journal, 2024)
Patients with acute ST-elevation myocardial infarction (STEMI) are at risk for conduction abnormalities and bradyarrhythmias, which may necessitate the use of a temporary pacemaker (TP). While TPs can stabilize patients, in-hospital outcomes, particularly mortality and arrhythmic complications, remain concerns. Understanding these outcomes in STEMI patients requiring TP can provide insights into timely interventions and guide clinical management. Objective: .To evaluate the in-hospital outcomes of patients with acute ST-elevation myocardial infarction (STEMI) requiring temporary pacemaker (TP) insertion, examine patient demographics, clinical presentation, laboratory parameters, timing of pacemaker intervention, and associated complications. Methods: This cross-sectional study included 90 patients with confirmed STEMI, treated in the cardiology department of a tertiary care hospital. Patients were eligible if they presented with acute STEMI and required TP due to conduction abnormalities or bradyarrhythmias unresponsive to pharmacological therapy. In-hospital outcomes, including mortality and arrhythmic complications (ventricular tachycardia, ventricular fibrillation, asystole) were recorded. Results: The mean age was 51.14 ± 6.18 years, with a predominance of males (64.4%). TP was inserted at presentation in 47.8% of patients and on the first post-MI day in 52.2%. In-hospital mortality occurred in 7.8% of cases, while ventricular tachycardia, ventricular fibrillation, and asystole were observed in 27.8%, 5.6%, and 2.2% of patients, respectively. Conclusion: Patients with STEMI requiring TP have substantial in-hospital mortality and a high rate of arrhythmic complications, particularly ventricular tachycardia. The findings underscore the importance of early intervention in cases with high risk of conduction abnormalities, emphasizing the value of TP in managing unstable STEMI cases.